PENGEMBANGAN MIND MAP PADA POKOK BAHASAN MOMENTUM, IMPULS, DAN TUMBUKAN - Alifa Juliana; Sri Wahyuni; Rayendra Wahyu Bachtiar (FKIP Universitas Jember, 2017)
The purpose of this research were: (1) describing the logical validity of mindmap product on the topic momentum, impuls, and collision, (2) describing studentlearning result in using of mind map product on the topic momentum, impuls, andcollision, (3) describing the student response after using of mind map product on thetopic momentum, impuls, and collision. The type of this research was developmentresearch in SMAN 2 Jember. Data collection methods used were documentation,observation, interview, and test. Data analysis techniques used were validationinstrument, drew mind map for student learning result, and percentage of studentresponses. The result of the research were: (1) the validity of product mind map bythe validators were 4,52 and quite valid, (2) the percentage of classical completenesswas 97,2% fall into the category of very good, (3) the students respons after learningwith mind map 82%. The conclusion by development mind map on the topicmomentum, impuls, and collision were the logical validity was valid, the studentlearning result was very good and the students respons gave positive category.Keyword: Mind Map, Student Learning Result, Momentum Impuls Collision.